2007
DOI: 10.1359/jbmr.070710
|View full text |Cite
|
Sign up to set email alerts
|

20(S)-Hydroxycholesterol Inhibits PPARγ Expression and Adipogenic Differentiation of Bone Marrow Stromal Cells Through a Hedgehog-Dependent Mechanism

Abstract: Specific oxysterols have been shown to be pro-osteogenic and anti-adipogenic. However, the molecular mechanism(s) by which oxysterols inhibit adipogenic differentiation is unknown. We show that the anti-adipogenic effects of osteogenic oxysterol, 20(S)-hydroxycholesterol, are mediated through a hedgehogdependent mechanism(s) and are associated with inhibition of PPAR␥ expression.Introduction: Multipotent bone marrow stromal cells (MSCs) are common progenitors of osteoblasts and adipocytes. A reciprocal relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
71
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 67 publications
(74 citation statements)
references
References 54 publications
2
71
0
1
Order By: Relevance
“…This suggests that, in addition to LXR signaling, other adipogenic mediators may contribute to the inhibition of adipogenesis by 27HC observed in our study. Indeed, the previously reported anti-adipogenic activity of the oxysterol 20(S)-hydroxycholesterol is mediated predominantly through hedgehog signaling, despite the activation of LXRs at the same time, and is associated with inhibition of peroxisome proliferatoractivated receptor ␥ levels (64). Another mechanism for 27HC action in adipocytes may involve interaction with ERs.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that, in addition to LXR signaling, other adipogenic mediators may contribute to the inhibition of adipogenesis by 27HC observed in our study. Indeed, the previously reported anti-adipogenic activity of the oxysterol 20(S)-hydroxycholesterol is mediated predominantly through hedgehog signaling, despite the activation of LXRs at the same time, and is associated with inhibition of peroxisome proliferatoractivated receptor ␥ levels (64). Another mechanism for 27HC action in adipocytes may involve interaction with ERs.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, oxLDL and 7κ-C were also reported to impair (pre) adipocyte differentiation and induce IR in mature adipocytes [104,117,118]. On the other hand, as previously mentioned, oxysterols can also behave as antiadipogenic signals by diverting pluripotent mesenchymal cells′ fate away from adipogenic and in favor of the osteogenic lineage through transactivation of Wntmediated signaling pathway [90,104,119].…”
Section: Oxysterolsmentioning
confidence: 91%
“…In human marrow stromal cells, specific products of cholesterol oxidation, namely the oxysterols (see below), have also importantly been implicated as endogenous signals modulating lineage-specific differentiation in favor of osteogenesis and against adipogenic differentiation [90,91]. Even more, the oxysterol-associated antiadipogenic actions were consistently linked with selective activation of Wnt target genes [92].…”
Section: Redox Regulation Of Wnt and Mapks At The Interface Between Omentioning
confidence: 99%
“…Moreover, the SHH protein can cause changes in endosteal hematopoietic stem cell niche, including osteoblasts, and thereby alter early lymphoid differentiation (Kiuru et al, 2009). It has also been shown that SHH protein or oxysterols, certain naturally occurring oxygenated derivatives of cholesterol, including 20(S)-hydroxycholesterol, can induce the antiadipogenic and osteogenic effects on multipotent BM-stromal cells by activating the canonical Hh pathway through SMO signaling element (Kim et al, 2007a(Kim et al, , 2010Amantea et al, 2008). In fact, the osteogenic effect induced through the stimulation of the Hh cascade seems to be mediated, at CRITICAL ROLES OF HEDGEHOG AND EGFR least in part, via the enhanced expression of gene products associated with the Notch (HES-1, HEY-1, and HEY-2) and Wingless (Dkk-1) pathways (Amantea et al, 2008;Kim et al, 2010).…”
Section: Functions Of the Sonic Hedgehog Protein In The Bone Marrow Amentioning
confidence: 99%